2006 IEEE International Symposium on Industrial Electronics 2006
DOI: 10.1109/isie.2006.296083
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Grip-Patterns by Using Capacitive Touch Sensors

Abstract: A novel and intuitive way of accessing applications of mobile devices is presented. The key idea is to use grip-pattern, which is naturally produced when a user tries to use the mobile device, as a clue to determine an application to be launched. To this end, a capacitive touch sensor system is carefully designed and installed underneath the housing of the mobile device to capture the information of the user's grip-pattern. The captured data is then recognized by a minimum distance classifier and a naive Bayes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…They showed that every digit could apply pressure accurately, but not equally. While not providing active input to the system, capacitive sensors around the edges of a mobile device have been used to detect hand posture [1]. Back-ofdevice interaction [13] avoids occlusion issues but input is generally limited to one digit during one-handed use.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that every digit could apply pressure accurately, but not equally. While not providing active input to the system, capacitive sensors around the edges of a mobile device have been used to detect hand posture [1]. Back-ofdevice interaction [13] avoids occlusion issues but input is generally limited to one digit during one-handed use.…”
Section: Related Workmentioning
confidence: 99%
“…When holding a mobile device one-handed, all five digits may be in contact around its edges, so there is an opportunity to provide multiple inputs from several digits simultaneously. Capacitive sensing around the device can be used to detect the location of digits and be used to change the current mode or function [1]. However, capacitive input is generally limited to binary input: either contact is made or it is not.…”
Section: Introductionmentioning
confidence: 99%
“…Back of device interaction also allows the creation of grasp-based technique that could predict users' intention by the way they hold the device. For instance, GripLaunch [2,5] is a tangible user interface that recognises a set of predefined hand grips and associated them with an application. For example grasping a mobile device horizontally with both hands can be associated with the camera or game applications.…”
Section: Related Workmentioning
confidence: 99%
“…A parallel, independent study performed at the Samsung Advanced Institute of Technology (SAIT) provided further validation for this method of grasp recognition [2,3]. Using a different device geometry and set of device modes, they achieved similar recognition accuracies across a variety of classifiers.…”
Section: Related Workmentioning
confidence: 99%